Evaluation of Low Vision and Blindness at the Federal Teaching Hospital, Gombe - Anozie, Kingsley Ononogbu; Ejukonemu, Barbie Monday; Odeh, Samuel Odu (Faculty of Natural and Applied Sciences Journal of Health, Sports Science and Recreation, 2025)
Low vision and blindness are significant global health concerns that affect millions of individuals, impacting their ability to perform daily activities and participate fully in society. Low vision refers to a visual impairment not fully correctable by standard glasses, contact lenses, medication, or surgery, and that interferes with normal functioning. Blindness typically involves a more severe level of vision loss, ranging from profound impairment to complete loss of sight. The causes of low vision and blindness are diverse and include age-related conditions such as macular degeneration and glaucoma, congenital or hereditary disorders, injuries, and systemic diseases like diabetes. This study aimed to evaluate the prevalence and causes of low vision and blindness at Federal Teaching Hospital Gombe (FTHG), Northeastern Nigeria. A total of 7040 participants who gave their informed consent were recruited and evaluated at the Optometry Unit. Results showed that the prevalence of low vision and blindness was 9.46% and 0.07%, respectively. Glaucoma (28.5%), refractive errors (23.2%), and maculopathy (14.9%) were the leading causes of low vision. Glaucoma was the sole cause of blindness. Age was significantly associated with low vision (P<0.05), but gender was not. Myopia was the most common refractive error (39.1%). This study highlights the need for early and improved eye care services and awareness in the region.